A Rare Case of Permanent Junctional Reciprocating Tachycardia Ablated on the Roof of the Left Atrium. (10th September 2012) - KALBFLEISCH, STEVEN J.; RHODES, TROY E.
<x xml:space="preserve">Abstract</x> A Rare Case of Permanent Junctional Reciprocating Tachycardia. Left‐sided anteroseptal accessory pathways that course through the aortomitral fibrous continuity are some of the rarest types of accessory pathways. At this region the atrium and ventricle are separated by their greatest distance because of the intervening aortic valve. These pathways often have a long circuitous course that may involve the root and cusps of the aortic valve. Prior reports have demonstrated the feasibility of ablating these pathways along the anteroseptal mitral annulus, the left ventricular outflow tract, or in the left or noncoronary cusps of the aortic valve. We describe a case of a concealed decremental anteroseptal accessory pathway that was ablated on the roof of the left atrium remote from the mitral or aortic valve annuli. This report indicates that when an appropriate site for ablation of a left‐sided anteroseptal accessory pathway is not found close to a valve annulus, these pathways may be amenable to ablation by targeting their atrial insertion site. (J Cardiovasc Electrophysiol, Vol. 24, pp. 464‐467, April 2013)